2007
DOI: 10.1063/1.2798910
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of hydrogen in wide band gap oxides

Abstract: The energy levels of interstitial hydrogen in various wide band gap oxides are calculated using a density function based method that does not need a band gap correction. The positive charge state has a large stabilization energy due to the formation of an O–H bond. The hydrogen level is found to be shallow in CdO, ZrO2, HfO2, La2O3, LaAlO3, SnO2, TiO2, SrTiO3, PbTiO3, and SrBi2Ta2O9, but deep in MgO, Al2O3, SiO2, ZrSiO4, HfSiO4, and SrZrO3. It is borderline in SrO. The predictions are found to agree well with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
97
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 51 publications
(50 reference statements)
12
97
0
Order By: Relevance
“…4,5 In order to investigate the discrepancy mentioned above, various kinds of functional were tested. The functional LDA, 26,36 PBE 22,27 and sX-LDA [30][31][32][33][37][38][39][40] were used in the DFT calculation. The valence states electrons of strontium were treated as 5s 2 , 4p 6 and 3d 2 states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 In order to investigate the discrepancy mentioned above, various kinds of functional were tested. The functional LDA, 26,36 PBE 22,27 and sX-LDA [30][31][32][33][37][38][39][40] were used in the DFT calculation. The valence states electrons of strontium were treated as 5s 2 , 4p 6 and 3d 2 states.…”
Section: Resultsmentioning
confidence: 99%
“…It, however, catches a little attention as no one has used the functional for structural phase transition prediction but for optical, 37,38 band gap, [32][33][34]38,39 band structure and electronic density of state. [32][33][34]38,40 Therefore, this work trailblazes the use of sX-LDA to find structural transition of solids which was validated by solving long-known computational experimental disagreement. Although sX-LDA is proven to be a qualified candidate for an alkaline-earth metal calculation, i.e., Sr, it should also be worth a try for calculation in other elements of this family, i.e., Mg, 42 …”
Section: -6mentioning
confidence: 99%
“…We attribute the large width of the peak, at least in part, to inhomogeneous charging effects (photoelectrons and secondary electrons). This is likely due to the large band gap of Al 2 O 3 (∆ = 8.8 eV 12 ) and its thickness of 4.4 ± 0.1 nm, which favor the presence of charge traps. As in the case of Cu 2 O, OH was also produced readily on the Al 2 O 3 surface at low RH.…”
Section: Al 2 O 3 Surface In the Presence Of H 2 Omentioning
confidence: 99%
“…Figure 12 shows the calculated CTL of hydrogen in several oxides reported in the literature. 97) It is found that low conduction band (CB) minimum measured from the vacuum level (i.e., large electron affinity) is required to form shallow donor states because the ¾(+/¹) level of hydrogen remains deep below the vacuum level. Because TAOS has a low CB minimum, it can change into semiconductor, which is totally different from SiO 2 (Fig.…”
Section: Mechanism Of Electron Dopingmentioning
confidence: 99%